The Reasons for Formula Feeding of Infants Under One Year of Age in Iran During 2011-2017 - Zohre Ahmadi; Zabiholah Gharlipour Gharghani; Leila Ghazvinian; Fateme Sadat Izadkhah (Mazandaran University of Medical Sciences, 2019)
Background: Considering the importance of breastfeeding and ignoring the exclusive breastfeeding in many cases, it is important to have knowledge of the reasons for formula feeding. In this regard, the purpose of this study was to evaluate the reasons for formula feeding in infants aged <1 year.  Methods: In this descriptive cross-sectional study, all records of infants aged <1 year (rural and urban) receiving formula feeding from 2011 to 2017 available in lactation counseling center located in Qom, Iran were examined and the reasons for their formula feeding was extracted. The extracted information was analyzed in SPSS V. 19 software. Results: Between 2011-2016, the most common reasons for formula feeding were unfavorable growth rate and twin/multiple pregnancy and the least common reasons were maternal death and parental separation in urban areas. The most common reason in urban areas was twin pregnancy (16.11%) and the least common was parental separation (0.27%) observed in 2017. In rural areas, the most common reasons were unfavorable growth rate and twin pregnancy between 2011-2016. In 2017, the most common reason was secondary-impact syndrome (22.3%) and the least common reasons were adoption and parental separation (0%).  Conclusions: There is a need to pay more attention to the attitude and knowledge of pregnant mothers about exclusive breastfeeding and reducing the use of infant formula.